STEMI: rare initial presentation of a mediastinal mass supplied by the RCA. Issue 12 (29th December 2019) - Claxton, Benjamin B; Loloi, Justin; Mrowczynski, Oliver D; Abdulbasit, Muhammad
Abstract : In the setting of severe septic shock, a 70-year-old woman had an ST segment myocardial infarction with ST elevations in the inferolateral leads. On cardiac catheterisation, no obstructive pathology was noted. Chest imaging revealed a large mediastinal mass measuring 8.5×6.5×7.5 cm in the visceral compartment of the mediastinum, with contrast enhancement from the right coronary artery (RCA). A biopsy was preformed and cytology was consistent with a well-differentiated neuroendocrine neoplasm. On review of the cardiac catherisation, it was noted that the mass was deriving blood supply from the RCA. Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a rare but well-documented phenomenon. In this case, MINOCA was caused by coronary steal syndrome in the setting of profound hypotension. Immediate management is with haemodynamic support; there is no role for coronary intervention.